Hubungan Antara Profitabilitas, Kebijakan Dividen, dan Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia Periode 2017-2022 - Kadir, Risnawaty; Selvi, Selvi; Mendo, Andi Yuniar (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The research aims to determine the relationship between profitability, dividend policy and company value in manufacturing companies in the basic industry and chemical sectors for the 2017-2022 period. The research method is quantitative with purposive sampling. The number of samples is 15 out of 86 companies in the basic industrial and chemical sectors. Data collection techniques use secondary data in the form of annual reports and financial reports. Research data analysis is multiple linear regression with hypothesis testing and correlation analysis between variables tested statistically. The test results show that partially Profitability has no significant effect on Company Value, while Dividend Policy has a significant effect on Company Value. Furthermore, simultaneously Profitability and Dividend Policy have a significant effect on Company Value. The results of the correlation test show that the degree of relationship between the three variables is in a very strong position because they influence each other.